Dietary Erucic Acid Induces Fat Accumulation, Hepatic Oxidative Damage, and Abnormal Lipid Metabolism in Nile Tilapia (Oreochromis niloticus) - Dingfei Ma; Qiangwei Li; Yuanyuan Xie; Youqin Kong; Zhili Ding; Jinyun Ye; Chenglong Wu; Yan Liu (Aquaculture Nutrition)
Erucic acid (EA) in rapeseed oil has adverse effects on terrestrial animal and fish health. However, its antinutritional role in fish remains unclear due to the limited information on EA. Therefore, this study was conducted to assess the impact of EA on growth performance, antioxidative capacity, fatty acid profile, and lipid metabolism in tilapia. Six diets containing different amounts of EA (0, 3, 6, 12, 20, and 27 g/kg diet) were fed to tilapia (initial weight: 3.01 ± 0.01 g) for 8 weeks. The results exhibited that dietary EA did not affect growth performance but remarkedly increased the crude lipid contents (in the whole body, liver, and muscle). It also markedly increased the levels of low-density lipoprotein cholesterol, total cholesterol, nonesterified fatty acids, and triglyceride in the liver and serum in a dose-dependent manner. The EA groups had lower values of total superoxide dismutase, total antioxidant capacity, catalase, and higher activities of aspartate aminotransferase and alanine aminotransferase, as dietary EA levels increased. Feeding fish with diets containing EA (20 and 27 g/kg diet) significantly increased the malondialdehyde content. Moreover, dietary EA greatly altered the fatty acid profile in the liver and muscle. It especially elevated the percentages of C18 : 2n-6, C20 : 1n-9, and C22 : 1n-9 while decreasing the C18 : 0 and C16 : 0 levels. When the levels of EA in diets were 12, 20, and 27 g/kg, genes correlated with lipophagy, lipolysis, and β-oxidation were significantly reduced. Meanwhile, genes concerned in triglyceride synthesis were largely increased in the liver and muscle. In summary, high-dose EA (20 g/kg diet) in the diets significantly induced fat accumulation, hepatic oxidative damage, and abnormal lipid metabolism in tilapia. The current findings expand our understanding on the antinutritional role of EA in lipid homeostasis and fish health.